Management of Education Quality Improvement at STKIP Bina Bangsa Getsampena of Banda Aceh - Rejeki, Rejeki; Yusrizal, Yusrizal; Usman, Nasir (Jurnal Pendidikan Progresif, 2021)
The purpose of this research is to see the management of improvement of education quality at STKIP Bina Bangsa Getsampena Banda Aceh, which includes program planning, implementation and supervision. Data collection techniques through: observation, interviews and documentation studies. The research subject includes the head of STKIP, vice chairman, lecturer, student. Data analysis by using data reduction, data presentation and withdrawal of conclusions. The results showed: The education quality improvement program is planned in the annual program and semester program, which is elaborated in the fields of general components, teaching, students, personnel, facilities and infrastructure, finance and cooperative relations. The implementation of the education quality improvement program is carried out through the application of the KKNI-based curriculum, the implementation of the Tridarma Perguruan Tinggi, improvement of learning facilities and infrastructures, requiring further study for educators, increasing collaboration and realizing transparency and accountability. Keywords: management, education, quality improvement, STKIP Bina Bangsa Getsampena DOI: 10.23960/jpp.v11.i2.202118